“Delinquents Often Become Criminals”: Juvenile Delinquency in Halifax, 1918-1935 - Boudreau, Michael (Acadiensis, 2010)
During the early part of the 20th century, juvenile delinquency in Halifax was perceived to be a serious social and moral problem that had to be solved without delay. Consequently, between 1918 and 1935, many of Halifax’s criminal justice officials fully embraced most facets of Canada’s modern juvenile justice system in order to deal with the local juvenile delinquents. By utilizing this new regulatory regime (notably the juvenile court and probation) to grapple with juvenile delinquency, Halifax was in the forefront, along with other cities, of the efforts to regulate and criminalize the lives of primarily poor, working-class children and their families. Résumé Au début du 20e siècle, la délinquance juvénile à Halifax était perçue comme un sérieux problème social et moral qu’il fallait résoudre sans tarder. Par conséquent, entre 1918 et 1935, de nombreux représentants de la justice pénale de Halifax endossèrent pleinement la plupart des facettes du système judiciaire moderne du Canada applicable aux jeunes afin de prendre des mesures contre les jeunes délinquants de l’endroit. En faisant appel à ce nouveau régime de réglementation (notamment le tribunal de la jeunesse et le système de probation des jeunes) pour lutter contre la délinquance juvénile, Halifax était à l’avant-plan, aux côtés d’autres villes, des efforts visant à réglementer et à criminaliser la vie d’enfants essentiellement pauvres et issus des milieux ouvriers, ainsi que de leurs familles.